Entre information et propagande : la Grèce dans la presse britannique et française pendant la Première Guerre mondiale - Elli Lemonidou (Revue LISA)
In this article, we present British and French propaganda during the First World War, whose aim was to shape and control, through the press, public opinion in these two countries. First, we examine the role of the official bodies responsible for propaganda, the Ministry of Information in Great Britain and the Maison de la presse in France, and the role of the censorship imposed on the press. This censorship was practised in a different way in the two countries, French censorship being much more rigorous than British. Next, we describe the image of Greece given through the English and French press during the First World War, specifying the events which the newspapers particularly concentrated on. We also mention the kind of information concerning Greek affairs which was banned by the censors. Finally, we present the various propagandist activities of the Greek government, notably its efforts to influence English and French journalistic circles, the subsidies given to newspapers and the creation of telegraphic agencies.